Cities in an era of interfacing infrastructures: Politics and spatialities of the urban nexus. (August 2019) - Monstadt, Jochen; Coutard, Olivier
Over the last few years, nexus-thinking has become a buzzword in urban research and practice. This also applies to recent claims of greater integration or coordination of urban infrastructures that have traditionally been managed separately and have been unbundled. The idea is to better address their growing sociotechnical complexity, their externalities and their operation within an urban system of systems. This article introduces a collection of case studies aimed at critically appraising how concepts of nexus and infrastructure integration have become guiding visions for the development of green, resilient or smart cities. It assesses how concepts of nexus and calls for higher interconnectivity and 'co-management' within and across infrastructure domains often forestall more politically informed discussions and downplay potential risks and institutional restrictions. Based on an urban political and sociotechnical approach, the introduction to this special issue centres around four major research gaps: 1) the tensions between calls for infrastructure re-bundling and the urban trends and realities driven by infrastructure restructuring since the 1990s; 2) the existing boundary work in cities and urban stakeholders' practices in bringing fragmented urban infrastructures together; 3) the politics involved in infrastructural and urban change and in aligning urban infrastructures that often defy managerial rhetoric of resource efficiency, smartness and resilience; and 4) the spatialities at play in infrastructural reconfigurations that selectively promote specific spaces and scales of metabolic autonomy, system operation (and failure), networked interconnectivities and system regulation. We conclude by outlining directions for future research.